ANALYSIS OF AQUIFER CONDITIONS OF GROUNDWATER BASIN BASED ON ESTIMATION OF AQUIFER PHYSICAL CHARACTERISTICS USING TIME LAPSE MICROGRAVITY DATA AND GROUNDWATER LEVEL DECREASE (CASE STUDY: CICENDO, MARGAHAYU, AND UJUNG BERUNG DISTRICT, BANDUNG, WEST JAVA) - Ammar Faruq, Sulthan
Every living thing needs clean water in the continuity of life. The development of an area is in line with the increasing need for clean water. The rapid pace of development of Bandung in every sector of life causes the need for clean water continues to increase. The need for clean water is still dependent on groundwater resources. The use of groundwater resources as a source of clean water can have a negative impact on the surrounding environment and if not used carefully can cause disasters in the future. Therefore, research needs to be conducted to find out what the condition of subsurface groundwater source is. Time lapse microgravity force is one of the methods that can be used for such purposes. This study models the groundwater conditions below the surface by estimating the physical characteristics of the aquifer using time-lapse microgravity data and groundwater depletion data. Estimation using Theis method. The data has some drawbacks thus lowering the level of accuracy. Modeling is carried out with SimQuring program based on forward modeling with a quadrilateral prism approach. Modeling was conducted in 3 places representing 3 geological formations of Bandung. The result of modeling is that all three research places have aquifers with depressed and deep aquifer types. This modeling also reveals the fact that the discharge of groundwater intake in the area studied is in the range of 450-600 (m3/day) and is classified as high. With a high groundwater discharge, resulting in an imbalance between water taken to the surface and water that enters the aquifer thus storing various potential disasters.